THE EFFECT OF SUBMERSION IN ORANGE JUICE AND FERMENTED MILK ON COLOR CHANGES OF NANOHIBRID COMPOSITE RESIN - Attila Yulaicha; Diah Ajeng Purbaningrum; Dwi Retnoningrum; Ariosta Ariosta (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Color changes in nanohibrid composite resins can occur due to 2 factors, intrinsic and extrinsic factors. Beverage can be the one of the extrinsic factor such as orange juice and fermented milk. The pH content of this both of drink will affect the change in color of the composite resin. Low pH conditions will cause the release of H+ which has an impact on the degradation and breaking of polymer chain bonds. Aim: To determine the effect of orange juice and fermented milk on the color change of nanohibrid composite resin. Methods: An experimental study with the post test control group design and a total sample of 6 samples. Soaking for 24 hours at 37ºC in artificial saliva, orange juice, and fermented milk. After 24 hours the color changes were measured using a colorimeter. Statistical test using Independent T-test.Results : Significant differences in color changes in nanohibrid composite resins between the two sample groups (p = 0.00). Independent T-test showed the results of a significant difference between 2 groups.Conclusion: Orange juice affect the change in color of nanohibrid composite resin. There was a significant difference between orange juice and fermentedKeywords: Nanohibrid composite resin, Color change, Orange juice, Fermented milk.